Homomorphisms and derivations on C*-ternary algebras assocoated with a generalized Cauchy-Jensen type additive functional equation (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In this paper, we prove the generalized Hyers-Ulam stability of C∗-ternary homomorphisms and C∗-ternary derivations on C∗-ternary algebras associated with the generalized Cauchy-Jensen type additive functional equationfor all xi; xj ∈ X where n ∈ Z+ is a fixed integer with n ≥ 3.